Formulation development of paracetamol instant jelly for pediatric use - Almurisi, Samah Hamed; Doolaanea, Abd Almonem; Akkawi, Muhammad Eid; Chatterjeed, Bappaditya; AL-japairai, Khater Ahmed Saeed; Sarker, Zaidul Islam (Taylor & Francis, 2020)
Objective: Paracetamol is a common antipyretic and analgesic medicine used in childhood illness by parents and physicians worldwide. Paracetamol has a bitter taste that is considered as a significant barrier for drug administration. This study aimed to develop an oral dosage form that is palatable and easy to swallow by pediatric patients as well as to overcome the shortcomings of liquid formulations.